CURRENT STATUS AND KNOWLEDGE-PRACTICE REGARDING PITYRIASIS VERSICOLOR AMONG PATIENTS AT HAI PHONG DERMATOLOGY CENTER IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of Pityriasis versicolor among patients presenting with clinical lesions at the Hai Phong Dermatology Center in 2025 and to describe the knowledge and practices regarding the disease among the study subjects.Methods: A cross-sectional descriptive study was conducted on 288 patients at the Hai Phong Dermatology Center. Data were collected through clinical examinations, direct microscopic examination with 10% KOH solution for definitive diagnosis of Pityriasis versicolor, and Knowledge-Attitude-Practice (KAP) interviews.Results: The prevalence of Pityriasis versicolor among patients with clinical lesions was 35.8%. The highest incidence was observed in children under 10 years old and the working-age group of 20–39 years old (both accounting for 27.2%). Regarding knowledge: 69.7% of subjects were aware of the causative pathogen and 94.2% recognized itching as a symptom; however, awareness of other symptoms remained low (itchiness increasing with perspiration: 23.2%; pigmentary/site changes: 48.5%). Knowledge of prevention reached 64.7%, with awareness of not sharing clothes being predominant (97.5%). Regarding practices: 40.7% of subjects still reported sharing clothes, and only 8.3% maintained the habit of showering after exercise. The rate of soap usage during bathing was 78.4%.
Keywords: Pityriasis versicolor, knowledge, practice, Hai Phong.